TheU-shape association between on-admission resting heart rate and 60-day all-cause mortality of AIDS inpatients in Fujian China: a retrospective cohort study - Rui Huang; Yan Li; Ling Chen; Yan Yang; Jinxiu Wang; Huan Zhao; Lifen Han (AIDS Research and Therapy)
Abstract Background An elevated resting heart rate (RHR) is associated with poor outcomes in both healthy individuals and those with human immunodeficiency virus (HIV) or acquired immunodeficiency syndrome (AIDS). This study aimed to investigated the association between on admission resting heart rate (RHR) and 60-day mortality. Methods This single-center retrospective cohort study evaluated the effect of RHR on the 60-day mortality of patient with AIDS in Southeast China. A total of 2188 patients with AIDS admitted for the first time between January 2016 and December 2021 were included. The RHR was categorized into tertiles. Disease progression was estimated using 60-day mortality rates. Cox proportional hazards regression models were used to evaluate the RHR with disease progression, and a two-piecewise Cox regression model was used to reveal the RHR effect at admission on 60-day mortality. Results We observed a U-shape relationship between RHR and 60-day mortality. For a above 90 bpm, the 60-day mortality rose rapidly with a multivariable adjusted odds ratio (OR) of 1.032 (95% confidence interval [CI 1.016–1.048, P < 0.001). Below the threshold, 60 days mortality decreased as the RHR increased to 90 bpm with a multivariate-adjusted OR of 0.943 (95% CI 0.904–0.984, P = 0.0065). Conclusions This study identified a U-shape relationship between RHR and 60-day mortality in HIV/AIDS patients. Further research is needed to characterize the role of RHR in the timely prevention of mortality in HIV/AIDS patients.